Dynamics of Islamic Family Law in Facing Current Challenges in Southeast Asia - Nasohah, Zaini (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Shariat contains rules appropriate for facing challenges at all times. It encompasses all aspects of human life including family laws. Family law as one of the important components in fiqh is based on evidence that is of juz’i and tafsili nature. This makes Islamic family law something dynamic. This article aims to view the position of Islamic family law in fiqh. It also intends to analyze the dynamicity of Islamic family law in facing current and future challenges, especially in Southeast Asia. Analysis was done through the content analysis method as descriptive and comparative. The findings of the analysis explained that Islamic family law is revealed in various forms of law bands appropriate to the current needs of the Islamic world. However, it is still in its basic framework which is to build a family system and consequently human social system based on Islamic law. Therefore, this dynamicity makes it remain relevant in facing current challenges. This study aims to analyze the dynamics of Islamic family law in facing current and future challenges. The analysis was made using descriptive and comparative content analysis methods. The results of the analysis explain that Islamic family law has been implemented in various forms and regulatory channels that are by the problems of the Islamic world. However, the rule is still within its basic framework, which is to compile the family system and so on the human social system based on Islamic law. Rather, it is this dynamic that makes it eternal and relevant to be ahead in facing today's challenges. The article also concludes that the Islamic family law that the state has fixed is dynamic with social and customary realities such as marriage, divorce, and women's and children's rights, especially in Southeast Asia.